A floating liner facility and studies of friction at a reciprocating piston-cylinder wall interface - Islam, Md Rezaul (2016)
The piston-cylinder liner interface comprises more than half of the total engine rubbing friction. With current demand being for internal combustion engines with better fuel economy, lower exhaust emissions and higher performance, reducing this form of friction is the subject of much study. The research reported in this thesis is concerned with the development of an existing floating liner rig to measure the friction in this region. The performance features of the modified setup have also been assessed. Parametric studies have been undertaken with the modified setup to identify the potential means of friction reduction. Modifications undertaken in the sealing method and driveline assembly has facilitated friction measurement at higher gas loading of up to 80 barg. The modified sealing assembly with a sealing ring overcame the problem of arbitrary force interruption through irregular liner and seal contacts. Addition of five times higher inertia flywheel aided the motor to support the rig with adequate torque during high gas loading operations. Calibrations have been performed at each different build of piston-liner combination to reduce build to build variability in measurement. Experimental studies have been undertaken to assess the friction characteristics for different factors such as operating pressure, temperature and speed, lubricant oil formulation, piston-liner clearance, piston material etc. Tests have been undertaken at a range of operating conditions; peak pressure of 0 to 80 barg, speed of 1000 to 2000 rpm and average mid-liner temperature of 40 to 90 ˚C. Peak cylinder pressure has been observed to be dominating the friction followed by temperature and speed. Friction spikes were observed near the top dead centre for pressurised operations; where normal load on the rings are highest in a cycle. Higher speed generally results in a higher total frictional loss. However at higher temperature and peak pressure, contrasting effect of speed on total friction has been reported. The study further identified that piston motion play important roles in determining mixed/boundary friction along with the local gas pressure, velocity and oil film temperature. Friction reductions have been obtained by using a lower viscosity oil and higher piston-liner clearance. Maximum friction reduction of 18% has been reported in this study by using SAE 0W-30 oil in place of SAE 5W-30. Diametric clearance of 80 μm obtained a maximum reduction of 12% compared to a lower clearance of 20 μm. The use of steel piston has shown potential in reducing friction over aluminium piston but the design and weight of piston played a dominant role in the frictional loss.